New insights into the relationships between egg maternal components: the interplays between albumen steroid hormones, proteins and eggshell protoporphyrin - Gvoždíková Javůrková, Veronika; Mikšík, Ivan (My University, 2023)
Recent studies have shown that the egg yolk maternal components, which are a mixture of substances that can affect the developing embryo, do not act separately but are interconnected and co-adapted. Surprisingly, no study to date has focused on the associations between maternally derived albumen steroids and albumen and eggshell compounds with pleiotropic effects. Eggshell pigment protoporphyrin (PROTO IX) should provide primary antimicrobial protection for eggs, but as a proven pro-oxidant, it may compromise female fitness. Abundant albumen proteins ovotransferrin (OVOTR) and lysozyme (LSM) have been shown to have antimicrobial, antioxidant, immunoregulatory and growth-regulatory roles. To investigate associations between albumen steroids and OVOTR, LSM and eggshell cuticle PROTO IX, we used chicken eggs with differently pigmented eggshells. We found that albumen steroid hormones were strongly intercorrelated. In addition, we revealed that albumen LSM and testosterone (T) were positively associated, while a negative association was found between albumen LSM and pregnenolone (P5). Eggshell cuticle PROTO IX was negatively associated with the concentration of albumen 17α-hydroxypregnenolone (17-OHP5). Finally, of all the hormones tested, only the concentration of albumen 17-OHP5 correlated negatively with egg volume and varied with eggshell colour and chicken breed. Although experimental evidence for the effect of maternal albumen steroids on avian developing embryo is still scarce, our study is the first to highlight co-variation and potential co-adjustment of maternally derived albumen steroids, proteins and eggshell cuticle pigment suggesting similar allocation mechanisms known for yolk maternal compounds with the potential to influence the avian embryo and offspring phenotype.
Nové poznatky o vztazích mezi vaječnými mateřskými složkami: interakce mezi steroidními hormony albuminu, proteiny a protoporfyrinem ve skořápce
Keywords: Antimicrobials; Hormones; Maternally derived egg components; Precocial birds; Eggshell pigmentation; Antimikrobiální látky; hormony; mateřské složky vajec; prekociální ptáci; pigmentace vaječných skořápek